2023
DOI: 10.1002/bab.2502
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic and anticoagulant efficiencies of purified fibrinolytic enzyme produced from Cochliobolus hawaiiensis under solid‐state fermentation

Medhat Ahmed Abu‐Tahon,
Ahmad Mohammad Abdel‐Majeed,
Mohamed Ghareib
et al.

Abstract: Cochliobolus hawaiiensis Alcorn Assiut University Mycological Centre 8606 was chosen from the screened 20 fungal species as the potent producer of fibrinolytic enzyme on skimmed‐milk agar plates. The greatest enzyme yield was attained when the submerged fermentation (SmF) conditions were optimized, and it was around (39.7 U/mg protein). Moreover, upon optimization of fibrinolytic enzyme production under solid‐state fermentation (SSF), the maximum productivity of fibrinolytic enzyme was greatly increased record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
(155 reference statements)
0
1
0
Order By: Relevance
“…The rate of blood clot dissolution exceeded 50% within 150 min and surpassed 80% within a period of 24 h. The results of in vitro clot lysis indicated that CFE exhibits significant thrombolytic activity. CFE exhibited similar activity to fibrinolytic enzymes from Cochliobolus hawaiiensis [41] and Bacillus subtilis DC33 [42], which have previously been reported to possess the ability to dissolve blood clots.…”
Section: In Vitro Fibrinolytic Effect Of Cfe On Blood Clotsmentioning
confidence: 64%
“…The rate of blood clot dissolution exceeded 50% within 150 min and surpassed 80% within a period of 24 h. The results of in vitro clot lysis indicated that CFE exhibits significant thrombolytic activity. CFE exhibited similar activity to fibrinolytic enzymes from Cochliobolus hawaiiensis [41] and Bacillus subtilis DC33 [42], which have previously been reported to possess the ability to dissolve blood clots.…”
Section: In Vitro Fibrinolytic Effect Of Cfe On Blood Clotsmentioning
confidence: 64%